Dynamic supramolecular polymers built from cucurbit[n]urils and viologens. Issue 4 (26th October 2018) - Correia, Henrique Dias; Chowdhury, Shagor; Ramos, Ana Paula; Guy, Laure; Demets, Grégoire Jean‐François; Bucher, Christophe
Abstract: This review article focuses on supramolecular assemblies involving cucurbit[ n ]uril‐based containers and viologen guests as key building elements. Cucurbit[ n ]urils (CB[ n ], n  = 5–8, 10) are fascinating hosts forming a wide range of inclusion complexes (caviplexes) with 4, 4′‐bipyridinium salts, known as viologens, either as discrete 1:1 inclusion compounds with CB[7] or as ternary inclusion compounds involving two hosts or two guests (2:1 with CB[7] and 1:2 or 1:1:1 with CB[8]). This property is currently being actively exploited to design and prepare self‐assembled dynamic stimuli‐responsive supramolecular polymers including gels, vesicles, films and organized arrays of polymeric microspheres or nanoparticles. This review highlights the main benefits of such polymers and gives an overview of the achievements and progress made in this field over the past decades. © 2018 Society of Chemical Industry Abstract : The scope of this review is to highlight the strategies which have been implemented to promote the formation of self‐assembled supramolecular polymers from cucurbit[ n ]uril (CB[ n ]) hosts and viologen guests, used as key building elements. The first part provides an overview of the polymeric systems reported in the literature involving these two components. The second part is dedicated to the applications of these specific host–guest processes in 'soft material' science.